Crystal structure of 3-amino-2-ethylquinazolin-4(3H)-one - El-Hiti, Gamal A. (Acta Crystallogr E Crystallogr Commun, 2015)
The molecule of the title compound, C(10)H(11)N(3)O, is planar, including the ethyl group, as indicated by the N—C—C—C torsion angle of 1.5 (2)°. In the crystal, inversion-related molecules are stacked along the a axis. Molecules are oriented head-to-tail and display π–π interactions with a centroid-to-centroid distance of 3.6664 (8) Å. N—H⋯O hydrogen bonds between molecules generate a ‘step’ structure through formation of an R (2) (2)(10) ring.